2005
DOI: 10.1353/sof.2005.0122
|View full text |Cite
|
Sign up to set email alerts
|

Who Can You Turn To? Tie Activation within Core Business Discussion Networks

Abstract: We examine the connection between personal network characteristics and the activation of ties for access to resources during routine times. We focus on factors affecting business owners' use of their core network ties to obtain legal, Joan, financial and expert advice. Owners rely more on core business ties when their core networks contain a high proportion of men, are very dense, and have high occupational heterogeneity. We conclude with suggestions for future research and implications for other populations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 54 publications
3
77
1
5
Order By: Relevance
“…When the need arises, actors convert pre-existing dormant or latent ties into active relationships (Hurlbert, Haines, and Beggs, 2000;Levin, Walter, and Murnighan, 2011;Mariotti and Delbridge, 2012;Renzulli and Aldrich, 2005). A variety of factorssuch as the level of interpersonal trust (Renzulli and Aldrich, 2005;Smith, 2005), identification strength (McDonald and Westphal, 2003), interpersonal affect (Casciaro and Lobo, 2008), the structure of pre-existing core networks (Hurlbert et al, 2000), and aspects of formal and quasi-formal organizational structure (Srivastava, 2012a)-can all drive a wedge between the resources potentially accessible through networks and those actually tapped in a given situation.…”
Section: Constrained Agency and Network Actionmentioning
confidence: 99%
“…When the need arises, actors convert pre-existing dormant or latent ties into active relationships (Hurlbert, Haines, and Beggs, 2000;Levin, Walter, and Murnighan, 2011;Mariotti and Delbridge, 2012;Renzulli and Aldrich, 2005). A variety of factorssuch as the level of interpersonal trust (Renzulli and Aldrich, 2005;Smith, 2005), identification strength (McDonald and Westphal, 2003), interpersonal affect (Casciaro and Lobo, 2008), the structure of pre-existing core networks (Hurlbert et al, 2000), and aspects of formal and quasi-formal organizational structure (Srivastava, 2012a)-can all drive a wedge between the resources potentially accessible through networks and those actually tapped in a given situation.…”
Section: Constrained Agency and Network Actionmentioning
confidence: 99%
“…This views however against the discovery by others researchers that found women entrepreneurs' alters have formed the closely knit in their network [24]. Similarly, research found that women entrepreneurs' networks have higher degree in network density [25]. Another investigation however found that both genders depend on male contact to get an advice [21].…”
Section: Network Densitymentioning
confidence: 82%
“…For instance, women entrepreneurs tend to rely more on networks composed of family and friends than men (Renzulli and Aldrich, 2005), as they have fewer opportunities to connect to new customers and business partners. For ethnic minorities and immigrants, barriers to building rich business networks mainly involve culture and language.…”
Section: Box 1 Women In Research and Entrepreneurship Activitiesmentioning
confidence: 99%